PENGARUH PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) BERBANTUAN MIND MAP TERHADAP KEMAMPUAN MULTIPELREPRESENTASI SISWA PADA MATERI HIDROKARBON KELAS X SMA NEGERI 1 SUNGAI AMBAWANG - Margarita Medina Icha; Dedeh Kurniasih; Fitriani Fitriani (Universitas Muhammadiyah Pontianak, 2017)
ABSTRACTThe purpose of this research to determine a difference and the influence of cooperative learning model Numbered Heads Together (NHT) assisted Mind Map multiple representation the ability of students. This research was Quasi Experimental Research with research design Nonequivalent Control Group Design. Samples were selected used technique purposive sampling, the class X3 as an experimental class and the class X2 as a control class. Data collected techniques in this study was the measurement techniques, direct observation and communication techniques. Data collected used the achievement test, the observation sheet and questionnaire. Based on the results of data analysis used non-parametric test U-Mann Whitney obtained significant value 0.000 < 0.05 which showed that there was differences in the ability multiple representation control class and experimental class. Effect Size value obtained is 0.78 which belongs to the category of medium. It can be concluded that the cooperative learning model Numbered Heads Together (NHT) assited Mind Map affect the ability of students multiple representation with contribution as 28.23%.Keywords: Hydrocarbons, mind map, multiple representation, Numbered Heads Together